2020
DOI: 10.1002/jnr.24730
|View full text |Cite
|
Sign up to set email alerts
|

Sleep problems in Rett syndrome animal models: A systematic review

Abstract: Rett Syndrome (RTT, MIM 312750), a progressive neurodevelopmental disease, has an approximately incidence rate of 1 in 10,000 (Neul et al., 2010) in live female births. RTT becomes visible through a neurodevelopmental regression following 6 to 18 months apparent normal developmental period. Loss of acquired language skills, stereotypic hand movements, and comprehensive cognitive, social, motor skill

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 107 publications
(320 reference statements)
0
13
0
Order By: Relevance
“…Disruption in sleep continuity and efficacy are confirmed. Sleep abnormalities and an increased number of nocturnal awakenings were observed in all animal models ( 90 , 132 134 ). Sleep duration was investigated by three studies, that showed an unchanged percentage duration of sleep during the day, but Johnston et al reported a decrease of REM sleep cycles in mutants ( 135 , 136 ).…”
Section: Sleep Disorders In Rett Syndrome and Rett-related Syndromementioning
confidence: 95%
See 4 more Smart Citations
“…Disruption in sleep continuity and efficacy are confirmed. Sleep abnormalities and an increased number of nocturnal awakenings were observed in all animal models ( 90 , 132 134 ). Sleep duration was investigated by three studies, that showed an unchanged percentage duration of sleep during the day, but Johnston et al reported a decrease of REM sleep cycles in mutants ( 135 , 136 ).…”
Section: Sleep Disorders In Rett Syndrome and Rett-related Syndromementioning
confidence: 95%
“…A possible role of MECP2 has emerged in the circadian system and a possible correlation with sleep problems observed in RTT patients (128,129). Alteration in the circadian rhythms have been found also in the mouse model of CDKL5 deficiency disorders (130) (90,103,135). This could be traced back to the glutamatergic alteration found in MECP2-null mice, in which a biphasic trend in the expression of ionotropic glutamate N methyl-D-aspartate receptors (NMDARs) in the frontal cortex was shown, with an initial increased density in the young stage, progressively decreasing.…”
Section: Sleep Research In Both Animal Models and Humansmentioning
confidence: 97%
See 3 more Smart Citations